2010
DOI: 10.2174/138161210793292429
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Family Proteins as Therapeutic Targets

Abstract: The mitochondrion provides the stage for the interplay of molecular interactions that regulate apoptosis via the intrinsic pathway. The release of apoptogenic factors from this compartment constitutes a critical juncture in this apoptotic pathway. Regulation of the integrity of the outer mitochondrial membrane (OMM) is the task of the Bcl-2 family of proteins. A network of interactions between the various subgroups of the family decides the apoptotic fate of a cell and, as such, an imbalance within this networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 154 publications
0
20
0
Order By: Relevance
“…Bcl-2 prevents mitochondrial membrane disruption, and inhibits Cyto-C activation and that of other pro-apoptotic factors (Czabotar and Lessene, 2010). As shown in Figure 4H, ovariectomy markedly reduced the expression of Bcl-2 in the tibias of the vehicle treated OVX group as compared to that of the sham operated control group ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl-2 prevents mitochondrial membrane disruption, and inhibits Cyto-C activation and that of other pro-apoptotic factors (Czabotar and Lessene, 2010). As shown in Figure 4H, ovariectomy markedly reduced the expression of Bcl-2 in the tibias of the vehicle treated OVX group as compared to that of the sham operated control group ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mitochondrial dysfunction further facilitates NF-κB activation (Cherry and Piantadosi, 2015). Additionally, Bcl-2 affects the mitochondrial function by regulating Cyto-C release and blocking NF-κB activation (Czabotar and Lessene, 2010). Therefore, the present results may also indicate that FLL treatment regains the mitochondria function by inhibiting Cyto-C activation via resuming Bcl-2 expression, and then preventing NF-κB-p65 activation and phosphorylation via inhibiting Nox4 overexpression in OVX rats.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-survival Bcl-2 family proteins are currently being pursued in a number of cancer therapeutic discovery projects (46,58). Understanding the primary role of pro-survival proteins in inhibiting apoptosis is important not only for future compound development but also for understanding potential resistance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that p53 can bind the Bax gene promoter region and regulate Bax gene transcription [12,13]. The Bcl-2 protein family plays a critical role in the regulation of apoptosis [14]. Because we observed apoptotic changes in CRC cells, we analyzed the levels of P53, Bax and Bcl-2 in cells treated with pEGFP-N1-GADD45B and Si-GADD45B, respectively.…”
Section: Resultsmentioning
confidence: 99%